Europe and Southeast Asia: Corporate and Social Identities. Prospects for the Norms Diffusion - Fijałkowski, Łukasz (Europa i Azja Południowo-Wschodnia: tożsamość korporacyjna i społeczna. Możliwość rozprzestrzeniania się norm, 2010)
Different international relations theories explain the role of the EU and ASEAN' different ways. As they focus on the specific explanation, using their own methodology, and starting points, they differ in the assumptions and explanations. Among others, social constructivism tries to deal with the problem from its specific perspective, focusing on the idea of corporate and social identities. Those identities lead actors to define their interests in certain ways and display particular types of behaviour. Hence, the EU's and ASEAN's identities influence their interactions, and help to support/negate acceptation of different types of norms
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 152-162
Keywords: corporate and social identities; norms localization; ASEAN; European Union